Concentrated Light for Accelerated Photo Degradation of Polymer Materials. Issue 4 (6th December 2012) - Madsen, Morten V.; Tromholt, Thomas; Norrman, Kion; Krebs, Frederik C.
<x xml:space="preserve">Abstract</x> Concentrated light is used to perform photochemical degradation of polymer solar cell materials with acceleration factors up to 1200. At constant temperature the photon efficiency in regards to photo degradation is constant for 1–150 suns and oxygen diffusion rates are not a limiting factor. Accelerated degradation by concentrated light thus allows for rapid and precise evaluations of one sun polymer stabilities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>